Commentary on Aghion, Hart, and Moore, Improving Bankruptcy Procedure - Ian F. Fletcher (Washington University Law Quarterly, 1994)
I would consider it most unlikely that their radical model for determining the fate of insolvent companies will be incorporated into any legislative proposals that emerge from the current review. From the standpoint of most of the interested parties involved in the operation of U.K. insolvency law, Aghion, Hart, and Moore's suggested process of mandatory transubstantiation, whereby debt is converted into equity "on the stroke of midnight," as it were, is likely to prove too daunting both in conceptual and in practical terms.
Keywords: Bankruptcy law; International; Oliver Hart; Bankruptcy; Law & economics; Bankruptcy reorganization -- Great Britain